Plasmon Wave Propagation Property of Metal Wedge Plasmonic Waveguides Covered by a Protective Oxide Layer - Thuy, Vu Thi Ngoc; Hoang, Chu Manh (Communications in Physics, 2022)
Guiding plasmon waves is based on dielectric/metal interfaces. The wedge-shaped interface shows an excellent capacity in the tight lightwave confinement at deep-subwavelength propagation mode size. Several types of metals have also been investigated for guiding plasmon waves. Among them, the Ag metal shows a plasmon wave guiding ability superior to other metals, however, it is sensitive to the operating medium and is easily oxidized. To overcome these drawbacks, the Ag wedge covered by a protective thin oxide layer is proposed. Numerically investigated results show that the propagation length of the Ag wedge covered by a protective thin silicon dioxide layer can be enhanced by a factor of 7.5 while its figure of merit is at least 1.7 times larger than that of the Au wedge waveguide. The advantage of the proposed interface is potential for developing plasmonic waveguide components.